Democratic Backsliding - Case Study of Tunisia - Němcová, Petra (2024)
This Master Thesis analyzes the main causes and actors of democratic backsliding in Tunisia. The first chapter discusses democratic backsliding from a theoretical point ot view, together with relevant connections and developments. The second chapter talks about the main actors of democratic backsliding from a global and regional point of view; in this case the MENA region. The third chapter then discusses Tunisia's development towards contemporary political situation. Tunisia's chapter is based on the theoretical background from the two previous chapters as well as empirical insights.